O IPTU progressivo no tempo - Cunha, Nicodemos Victor Dantas da (2016)
The aim of the dissertation is to analyze the figure of PROPERTY TAX progressiveness in time within the Constitutional Tax context. Presenting the divergence in the approach to the tax rate growth, caused by failure of the real state owner to give attention to the social function of urban property. Some believe that such rate growth comes to sanction the unlawful act, hurting the concept of Tribute to Article 3 of the National Tax Code, on the other hand, some researchers believe that this growth is due to extrafiscality. In this way, this text seeks to define the figure of the penalty, in order to demonstrate the absence of sanction strictly speaking, and also seeks to define the extrafiscality, on the understanding that this is the case, exalting the important contribution made by such tax instrument in the regulation of human conduct. Furthermore, it is possible to see that, apparently, there's a point at which this last branch has no legal ability to coerce the real state owner to act according to the dictates of the Constitution, which now strikes the interdisciplinary importance on a dialogue with urban, constitutional and administrative laws. At last, the principle of the non-confiscation and its development with regard to the theme of this work, as well as some other particularities of the progressiveness in time of the PROPERTY TAX within the Brazilian Law structure, such as in the Statute of Cities (law nº. 10.257/01), as well as the legislation established in São Paulo, such as, the master plan of the city (law No. 16,050/2014) and the decrees n°. 55.638 of October 30th 2014, and nº. 56.589, of November 10th 2015